Catalytic Transfer Hydrogenation of Castor Oil Using Glycerol-Based Reaction - Mohd Amin, U.S.B. (Springer Science+Business Media B.V., 2020)
Abstract: A catalytic transfer hydrogenation of castor oil using glycerol-based is a process of adding hydrogen to the castor oil to produce hydrogenated castor oil with the addition of 10 Pd/C as the catalyst and glycerol as a hydrogen donor. The reaction occurred at the reaction temperature of 178Â Â°C for an hour. To prove whether glycerol can be one of the hydrogen donors like limonene that is commonly used, the research started by using pure glycerol as the hydrogen donor and as a control to determine the protocol. A direct heating apparatus connected with a reflux system was used for this experiment. The result from FTIR along with the melting point shows the formation of hydrogenated castor oil from this reaction. The increment in melting point value and the absence of C=C peak (1655.79Â cmâ1) from FTIR spectrum shows that the catalytic transfer hydrogenation successfully occurred. The melting point of the hydrogenated castor oil is 65Â Â°C and the melting point of castor oil is â 7Â Â°C. Therefore, it was proven that, the glycerol can be used as the hydrogen donor for the castor oil for a catalytic transfer hydrogenation reaction. Graphic abstract: Figure not available: see fulltext.. Â© 2020, Springer Nature B.V.